Exploring the prosociality domains of trust and cooperation, through single and cooperative digital gameplay in Path of Trust. - Konstantinos Cornelis Apostolakis; Athanasios Psaltis; Kiriakos Stefanidis; Kyriaki Kaza; Spyridon Thermos; Kosmas Dimitropoulos; Evangelia Dimaraki; Petros Daras (International Journal of Serious Games, 2016)
Amidst an ongoing debate surrounding the traditional dichotomy of whether video games are good or bad for children, in this paper we present Path of Trust, a novel, prosocial game that aims at helping children understand the importance of teamwork and learn how and when to express trustworthiness. We have created a colorful, non-violent digital game, in which children aged 7-10 can be exposed to prosocial content and develop specific prosocial attitudes, such as cooperation and trustworthiness, driven by the fact that video games with prosocial content can be used to improve social interactions. The game was designed to maintain an attractive and engaging nature, which is usually associated with games that are often vilified within social circles in terms of being packed with tons of action and violence. We conducted two separate studies to test our game’s modeling of prosocial behavior, which demonstrate the potential of the game as a tool for teaching important prosocial behavior to children.